Transformational Spiritual Learning in Umrah Guidance: A Participatory Immersion Spiritual Approach for Indonesian Umrah Pilgrims - Taufikin Taufikin (Publikasi Hasil Pengabdian kepada Masyarakat (PADIMAS), 2026)
Current Umrah pilgrim guidance emphasizes ritual procedures over spiritual learning, leaving the reflective and participatory aspects underdeveloped. To address this gap, this community service activity developed a participatory-reflective spiritual guidance model to enhance pilgrims’ religious learning during Umrah. The program engaged 127 pilgrims from PT Azzahra Berkah Ilahi in Demak Regency through reflective manasik, worship practice simulations, intensive guidance in Mecca and Medina, and post-worship spiritual reflection. Data were collected through participatory observation, reflective interviews, documentation, and field notes, and analyzed descriptively and reflectively. Findings reveal four main stages in pilgrims’ spiritual development: reflective orientation, embodied ritual learning, guidance in sacred spaces, and post-worship reflection and internalization. The Spiritual Participatory Immersion approach enables pilgrims to move beyond procedural ritual mastery to deep, reflective, and transformational learning. This study thus demonstrates a model that fosters a more humanistic, pedagogical, and spiritually transformative Umrah guidance